2011
DOI: 10.1126/science.1206376
|View full text |Cite
|
Sign up to set email alerts
|

A Single Molecule of Water Encapsulated in Fullerene C 60

Abstract: Water normally exists in hydrogen-bonded environments, but a single molecule of H(2)O without any hydrogen bonds can be completely isolated within the confined subnano space inside fullerene C(60). We isolated bulk quantities of such a molecule by first synthesizing an open-cage C(60) derivative whose opening can be enlarged in situ at 120°C that quantitatively encapsulated one water molecule under the high-pressure conditions. The relatively simple method was developed to close the cage and encapsulate water.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
493
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(523 citation statements)
references
References 32 publications
(36 reference statements)
22
493
2
6
Order By: Relevance
“…The downfield shift of 0.05 ppm relative to empty C 60 deviates from the empirical correlation drawn previously between the van der Waals radius of the endohedral guest and a downfield 13 C chemical shift (H 2 O@C 60 , 0.11 ppm; H 2 @C 60 , 0.08 ppm; He@C 60 0.02 ppm). 2,3,30 A series of 19 F NMR spectra of HF@C 60 in the polycrystalline solid state were acquired at 263 K, using magic-angle spinning at a range of rotation frequencies, without 1 H decoupling ( Figure 2 and Supplementary Figures 5 and 6). All spectra display a prominent splitting due to a 1 H-19 F J-coupling of 506 ± 0.5 Hz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The downfield shift of 0.05 ppm relative to empty C 60 deviates from the empirical correlation drawn previously between the van der Waals radius of the endohedral guest and a downfield 13 C chemical shift (H 2 O@C 60 , 0.11 ppm; H 2 @C 60 , 0.08 ppm; He@C 60 0.02 ppm). 2,3,30 A series of 19 F NMR spectra of HF@C 60 in the polycrystalline solid state were acquired at 263 K, using magic-angle spinning at a range of rotation frequencies, without 1 H decoupling ( Figure 2 and Supplementary Figures 5 and 6). All spectra display a prominent splitting due to a 1 H-19 F J-coupling of 506 ± 0.5 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…1 The dihydrogen and water endofullerenes H 2 @C 60 , H 2 O@C 60 , and their isotopologues, have been synthesized by the procedure known as 'molecular surgery', in which synthetic operations are used to open a hole in the fullerene allowing encapsulation of the guest, followed by a suturing technique to reform the pristine fullerene shell. [2][3][4] Recently the approach has been extended to C 70 and C 59 N. [5][6][7] The confined molecules display quantization of their coupled translational and rotational degrees of freedom, and exhibit phenomena such as nuclear spin isomerism and orthopara conversion. [8][9][10][11][12] Recently it was shown that nuclear spin conversion of the encapsulated water molecules in H 2 O@C 60 leads to a change in the dielectric constant of the material.…”
mentioning
confidence: 99%
“…Central to these studies is the notion that the displacement of a high-energy water cluster from a receptor drives guest association, and in some cases, subsequent catalysis. However, despite the abundance of structural data documenting diverse water clusters encapsulated in various host cavities, mechanistic descriptions of the dynamic processes between water and host are rare (24)(25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Besides H 2 @C 60 , the theoretical study of which will be reported shortly, this includes molecular hydrogen in clathrate hydrates [19,29,30], metal-organic frameworks [31][32][33][34][35] and zeolites [36,37], among others. Finally, methodological extensions are in progress in our group to the INS spectra of nanoconfined polyatomic molecules such as methane [38] and water [39].…”
Section: Discussionmentioning
confidence: 99%